Pengaruh Kualitas Pelayanan, Kualitas Produk, dan Persepsi Harga Terhadap Kepuasan Pelanggan - Salsa Agist Pritami; Surono Surono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to examine the effect of service quality, product quality, and price perceptions on customer satisfaction at Hotel Double Tree by Hilton Jakarta Diponegoro. customer satisfaction at Double Tree by Hilton Jakarta Diponegoro Hotel. Quantitative method method was used by conducting a survey of 100 hotel guests who have stayed more than once. more than once. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that service quality service quality has a significant influence on customer satisfaction, while product quality has no significant effect, and perceived price also has a significant effect on customer satisfaction. has a significant influence on customer satisfaction. Research results research results also show that service quality, product quality and price perceptions together have an effect on customer satisfaction.